School Psychology in Brazil - Van Kolck, Odette Lourenção [UNESP]; Barros, Celia Guimaraes (SAGE Publications, 1985)
A brief historical view of the education and of the somewhat new job of psychologist in Brazil, together with an analysis of the present situation of the school psychologist, shows substantial changes in this field. Data obtained from research carried out in primary schools in the city of Sao Paulo, focusing on the performance and the difficulties related to the school psychologist's work, training and professional situation, lead to the conclusion that it is necessary to define clearly the professional role of the school psychologist and to make both the population and the administration aware of their preventive activities. © 1985, Sage Publications. All rights reserved.